Pelatihan Case Method dan Team Based Project Guru IPS SMP Di Malang Raya Sebagai Solusi Mengatasi Demotivasi Siswa - Agus Purnomo; Khofifatu Rohmah Adi; Ike Ratnawati (Universitas Lambung Mangkurat, 2023)
This community service is carried out for social studies teachers throughout Malang Raya with the aim that social studies teachers can overcome student demotivation during distance learning through the case method and team-based project. This learning method has also been shown to be able to increase student motivation to participate in learning activities, which promotes learning and improves performance in assessments. This activity includes the stages of implementing mentoring, monitoring performance, and giving an impact on alumni who work as Social Studies Teachers for Middle Schools in Malang Raya. The stages of the activity include (1) assistance by a team of experts in Learning Evaluation at Universitas Negeri Malang, (2) practice of preparing learning tools, and (3) learning simulations using the Case Method and Team based Project. The results of this dedication show that the case method and team-based project can increase student motivation during distance learning. Therefore, the implications of this research can be used as a solution to the problems of the learning process so far related to student demotivation. So, social studies teachers in junior high school can implement this case method and team-based project training.